Os desafios para o ensino da literatura amapaense: relatos de professores de língua portuguesa e literatura da escola estadual Risalva Freitas do Amaral - (:unkn) unknown (Brasil, 2026)
This study analyzes the main challenges involved in teaching Amapaense literature, considering that literature teaching is currently facing a crisis of appreciation, as teachers report difficulties in stimulating students’ interest in reading practices. This crisis becomes even more pronounced when it comes to Amapaense literature, since, in addition to the challenges of motivating reading, it also faces unfamiliarity and prejudice regarding its themes. The methodology is based on bibliographic research, followed by the analysis of educational documents such as the National Common Core Curriculum (BNCC), the Amapaense Curriculum Reference (RCA), and the Political-Pedagogical Project (PPP) of the target school. Furthermore, data were collected through open-ended interviews with Portuguese Language and Literature teachers from the Risalva Freitas do Amaral State School, as well as through the analysis of the institution’s PPP with regard to the applicability and study of Amapaense literature. The research also highlights the importance of incorporating literary literacy, according to Rildo Cosson’s conception, into the teaching context of this literary modality, as well as the notion of literary enjoyment proposed by Teresa Colomer. In addition, it presents aspects of the history of Amapaense literature based on the studies of Francesco Marino, Manoel Souza, and Yurgel Caldas, thereby contributing to a more meaningful understanding of the investigated topic.
Keywords: Literatura; Letramento Literário; Ensino de Literatura; Literatura Amapaense; HUMANITIES and RELIGION::Aesthetic subjects::Literature; Literary Literacy; Teaching Literature; Amapaense Literature; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA